SURGICAL TREATMENT OF UPPER CERVICAL SPINE INJURIES (C1-C2): EXPERIENCE IN 26 PATIENTS: Cervical Spine Injuries - Pasha, Lt Col Ibrahim Farooq; Qureshi, Muhammad Asad; Qureshi, Muhammed Abid; Khalique, Ahmed Bilal; ., Wasim Afzal (Pakistan Armed Forces Medical Journal, 2013)
Objective: To describe the spectrum of operations in unstable upper cervical spinal injuries in (atlanto-axial) region at our unit.Study Design: A cross-sectional study.Place And Duration: Spine Unit, Department of Orthopedics, Combined Military Hospital (CMH), Rawalpindi from Jan 2001 to Dec 2008.Patients and Methods: Frequency of different kind of operations in 26 patients operated for upper cervical spinal injuries was reviewed. A performa was made for each patient and records were kept in a custom built Microsoft access database.Results: Average age of patients studied was 27 years with male pre dominance. Total 12(46%) patients had Atlanto-axial instability, 8(31%) had Hangman’s fracture and 6(23%) patients had odontoid peg fracture. While 11(42%) patients had no neurological deficit according to American spinal injury association impairment scale (AIS-E) and 15(58%) had partial neurological deficit. The patients were divided into three groups. Group A had odontoid peg fracture, Group B had atlanto-axial instability and Group C had Hangman’s fracture. The spine was approached posteriorly in 19(73%) cases and anteriorly in 7(27%). Pedicle screw fixation was done in 6(23%) patients, odontoid peg screw fixation in 6(23%), Gallie's fusion in 5(19%), occipito-cervical fusion in 4(15%), posterior transarticular fixation in 3(12%), anterior transarticular fixation and decompression in others, 9(60%) patients improved neurologically postoperatively and there was no deterioration of neurological status. Nonunion in two (8%) cases and implant failure in one (4%) were complications.Conclusion: Upper cervical injuries (C1-C2) are rare and their management is complex, necessitating lot of experience for their management. Early diagnosis and appropriate treatment is essential for good outcome. Each injury has to be managed at its own merit and a single operation may not be appropriate in all situations. General guidelines can be drawn from our study for the management of these cases on modern line.